Successful Treatment of Acute on Chronic Mesenteric Ischaemia by Common Iliac to Inferior Mesenteric Artery Bypass. (1st September 2015) - Coakley, D. N.; Shaikh, F. M.; Kavanagh, E. G.
Abstract : Chronic mesenteric ischaemia is a rare and potentially fatal condition most commonly due to atherosclerotic stenosis or occlusion of two or more mesenteric arteries. Multivessel revascularisation of both primary mesenteric vessels, the celiac artery and superior mesenteric artery (SMA), is the current mainstay of treatment; however, in a certain cohort of patients, revascularisation one or both vessels may not be possible. Arteries may be technically unreconstructable or the patient may be surgically unfit for the prolonged aortic cross clamping times required. Here we present a case involving a 72-year-old woman with acute on chronic mesenteric ischaemia. She was a high risk surgical patient with severe unreconstructable stenotic disease of the SMA and celiac arteries. She was successfully treated with single vessel revascularisation of the inferior mesenteric artery (IMA) via a common iliac to IMA reversed vein bypass. At two-year follow-up, the graft remains patent and the patient continues to be symptom-free and is maintaining her weight.